2019
DOI: 10.3389/fchem.2019.00496
|View full text |Cite
|
Sign up to set email alerts
|

Docking, Interaction Fingerprint, and Three-Dimensional Quantitative Structure–Activity Relationship (3D-QSAR) of Sigma1 Receptor Ligands, Analogs of the Neuroprotective Agent RC-33

Abstract: The human Sigma1 receptor (S1R), which has been identified as a target with an important role in neuropsychological disorders, was first crystallized 3 years ago. Since S1R structure has no relation with another previous crystallized structures, the presence of the new crystal is an important hallmark for the design of agonists and antagonists against this important target. Some years ago, our group identified RC-33, a potent and selective S1R agonist, endowed with neuroprotective properties. In this work, dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…A systematic and detailed analysis of all possible interactions between LasB and the docked NAMdP could be performed by using Interaction Fingerprints (IFPs). Previous studies have demonstrated that IFP analysis is a valuable tool that allowed for a better schematization of protein-ligand interactions [26,29,30].…”
Section: Molecular Docking Resultsmentioning
confidence: 99%
“…A systematic and detailed analysis of all possible interactions between LasB and the docked NAMdP could be performed by using Interaction Fingerprints (IFPs). Previous studies have demonstrated that IFP analysis is a valuable tool that allowed for a better schematization of protein-ligand interactions [26,29,30].…”
Section: Molecular Docking Resultsmentioning
confidence: 99%
“…In this section I am focused on identifying the recurrent interactions between ACE domain binding sites and their ligands, and the residues involved in these interactions. Interaction fingerprints (IFPs) is a very effective method for such analysis, with recent successful applications in diverse protein-ligand systems [84][85][86][87]. "Interaction Fingerprints Panel" of Maestro (Maestro 10.2.011, Schrödinger LLC) was used for constructing the IFPs as described in Singh et al [88,89].…”
Section: Interaction Fingerprints (Ifps) For Ace Inhibitors Derived Fmentioning
confidence: 99%
“…In turn, their smaller hydrophobic groups (most often, these are various substituents bonded to amine nitrogen) must be located near the Phe107, Trp164, His154, and Ile124 residues (these residues are included in the secondary hydrophobic site, see Figures S8 and S9 ). In general, Sigma1R ligand molecule includes: a large and small hydrophobic parts connected by a spacer (its length and nature may be different), and at least one amino group that is located somewhere in between these parts or near one of them [ 86 ]. It should be noted that structures of NE-100, (+)-pentazocine and fabomotizole molecules correspond to the abovementioned pharmacophore characteristics of Sigma1R ligands (summarized in Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of receptor grids was generated to define a ligand binding site for subsequent docking analysis. A grid box of 20 × 20 × 20 Å was created for each ‘ligand–receptor’ complex, centered on the center of mass of the ligand in the selected crystal structure, covering the binding site of Sigma1R [ 86 ]. A scaling factor of 1.0 and a partial charge threshold of 0.25 were used during the generation of the grid boxes.…”
Section: Methodsmentioning
confidence: 99%